The Analysis of Students’ Error in Operation Reseach Test for Linear Program Topic Based on Newman’s Error Analysis (NEA) - Mesi Oktafia; Aan Putra; Mhmd Habibi (Edumatika : Jurnal Riset Pendidikan Matematika, 2020)
Abstract. This study aims to analyze the types of error and its factors that cause students’ error in solving operation research problems in the program linear topic based on Newman’s Error Analysis (NEA). This research is qualitative research by using a descriptive approach. The subjects in this study are fourth-grade college students in the Mathematics Education Program at State Islamic Institute of Kerinci that chosen by purposive sampling technique. The data was collected by using a test and interview. The data analysis was done descriptively. Based on the research findings, the types of students error in solving operation research problems were reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The factors that cause the students' error were the students can not interpret, understand and understand the meaning of the questions overall; can not determine the formula to solve the problems; can not carry out the algorithm of arithmetic operations. Abstrak. Penelitian ini bertujuan untuk menganalisis jenis kesalahan dan faktor yang menyebabkan kesalahan mahasiswa dalam menyelesaikan soal riset operasi pada materi program linier berdasarkan Newman’s Error Analysis (NEA). Penelitian ini merupakan penelitian kualitatif dengan menggunakan pendekatan deskriptif. Subjek penelitian ini adalah mahasiswa semester IV program studi Tadris Matematika IAIN Kerinci tahun akademik 2018/2019 yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui tes dan wawancara dan dianalisis secara deskriptif. Berdasarkan temuan penelitian diketahui bahwa jenis kesalahan mahasiswa dalam menyelesaiakan soal riset operasi materi program linier berdasarkan Newman’s Error Analysis adalah kesalahan dalam membaca soal, kesalahan dalam memahami masalah, kesalahan dalam transformasi, kesalahan dalam keterampilan proses, dan kesalahan dalam penulisan jawaban akhir. Faktor-faktor penyebab kesalahan tersebut meliputi: mahasiswa tidak bisa memaknai, mengerti dan memahami makna keseluruhan dari soal yang berikan; tidak bisa menentukan rumus yang digunakan; dan tidak bisa menajalankan tahapan-tahapan operasi hitung yang digunakan untuk menyelesaikan soal.